SHORELAND DEVELOPMENT AND DISTURBANCES: A HEDONIC ANALYSIS OF LAKEFRONT PROPERTIES IN NORTHEASTERN WISCONSIN, USA - (:unkn) unknown (My University, 2024)
Shoreland development, encompassing features like boat lifts, manicured lawns, artificial beaches, and erosion control measures, offers considerable benefits to property owners. Nevertheless, this development disrupts natural conditions and is associated with increased sediment and pollutant loading, which negatively impacts aesthetics, recreation, and habitat for fish and other aquatic species. This thesis conducts two analyses, which respectively quantify the benefits of shoreland development to homeowners and evaluate the relationship between shoreland development and lake water quality. In the first analysis, a hedonic property model is employed to value shoreland development along Wisconsin inland lakes. The model considers various shoreland development features, using data from 62 lakes surveyed comprehensively under the Wisconsin Department of Natural Resources (WDNR) Lake Shoreland and Shallows Habitat Monitoring Program. Results show positive correlations between sales prices and certain development features, including artificial beaches, erosion control measures, and structures in the littoral zone, after controlling for housing characteristics and lake fixed effects. Willingness-to-pay values for these features are derived from the model; these values can be compared to the welfare loss stemming from sediment and pollutant loading caused by development to inform shoreland management decisions. In the second analysis, the effect of shoreland development on lake water clarity is evaluated. Results show that the extent of shoreland development on a lake is not significantly correlated with water clarity, after controlling for lake characteristic and nearby land use.
Keywords: hedonic; lakeshore disturbances; lakeshore habitat; property valuation; water clarity